Pembatasan Peserta Pemilu Oleh Komisi Pemilihan Umum - Andrian Habibi (UIN JAKARTA, 2020)
The Election Law instructs election administrators to organize electoral techniques. However, the law regarding the Formation of Legislation said that the discussion and issuance of a rule must refer to the hierarchical concept of legislation. If the technical rules of the election organizer exceed the authority stipulated in the Election Law, then a norm collision will emerge that impacts the norm confusion. This study uses a qualitative narrative study. By explaining the relationship between one legislation and the other. Researchers found the impact of the issuance of PKPU Number 11 in 2017 and the use of Sipol was the death of 13 political parties that registered as candidates for election. In this case, the KPU proved to be a failure, both in maintaining the legality and Sipol application.